Faithful Economics : 25 Short Insights - Finn, Daniel K., 1947- (Book collections on Project MUSE., 2021)
"Careful moral reflection and action are important across all of modern life, but they are especially critical when it comes to our place as individuals and communities in matters of economics. We know intuitively that our daily decisions about money and markets have a deep impact on others, but it is easy to become overwhelmed and confused or, worse, to feel as if our actions don't make a difference. Faithful Economics is the ideal guide for navigating this complex arena and coming to a deeper understanding of how our faith and our economic lives intersect. In twenty-five short lessons, each digestible in one brief sitting, the author explores a wide range of topics from lobbying and just wages to globalization and Catholic social teaching. Each section illuminates the issues, explains the questions, and leaves the reader with clarity and understanding. An ideal book for students, curious readers, and all who want to understand their place as a faithful participant in economic life." --